Cacos de uma história: reconstituição das vasilhas guarani - Faccio, Neide Barrocá [UNESP]; Toso, Diana Mirela da Silva [UNESP]; Luz, Juliana Aparecida Rocha [UNESP]; Matheus, Eduardo Pereira [UNESP]; Queiroz Junior, Alceu Alves [UNESP]; Cunha, Barbara Cardoso da [UNESP]; Rosa, Brendo Luiz Camargo [UNESP]; Gonçalves, Bruno Lucas [UNESP]; Andrade, Gustavo de Jesus [UNESP]; Vicente, Lívia Maria [UNESP]; Lima, Paula Cabral de [UNESP]; Gonçalves, Sinthia Silvestre [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
The restoration of broken pottery vessels, of archaeological value, it has been a practice of the Laboratory of Archaeology Guarani FCT/ UNESP, since 1988. This practice aims for exhibition in museums, pieces that were in boxes in the technical reserves of museums, intended for ignorance. This activity assists in the exhibition of collections and thus enables disclose the history of Indians who lived in our area and now can no longer tell their stories through words. The screen in outreach activity is held with the support of PROEX to museums in the state of São Paulo, for free.

O restauro de vasilhas cerâmicas quebradas, de valor arqueológico, tem sido uma prática do Laboratório de Arqueologia Guarani da FCT/UNESP, desde 1988. Essa prática visa colocar em exposição de museus, peças que antes estavam em caixas nas reservas técnicas dos museus e, assim, destinadas ao desconhecimento. Essa atividade auxilia na exposição de acervos e, dessa forma, possibilita divulgar a história de índios que viveram na nossa região e que hoje já não podem contar as suas histórias por meio de palavras. A atividade de extensão em tela é realizada com apoio da PROEX para museus do Estado de São Paulo, de forma gratuita.
Keywords: Reconstruction; Restoration; Archaeological ceramics; Reconstituição; Restauro; Cerâmica arqueológica